2023
DOI: 10.3389/fnagi.2023.1269952
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise combined with chlorogenic acid exerts neuroprotective effects and reverses cognitive decline in Alzheimer’s disease model mice (APP/PS1) via the SIRT1/ /PGC-1α/PPARγ signaling pathway

Dan Shi,
Zikang Hao,
Wenxiao Qi
et al.

Abstract: Alzheimer’s disease (AD) is a prevalent neurodegenerative disease account for 60–80% of the total number of people with dementia, but its treatment and prevention strategies are still in a long process of exploration. It has been reported that a healthy lifestyle may be an effective non-pharmacological intervention for the prevention and treatment of AD, including increased physical activity and the consumption of polyphenol-rich foods. This study, therefore, investigated the effects of 8 weeks of moderate-int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…PGC-1α is likely a pivotal target of SIRT1 due to its transcriptional regulation, with the associated transcription factors encompassing PPARα, PPARγ, FoxO1, Nrf1, Nrf2, etc. [66][67][68][69].…”
Section: The Link Between Neuroinflammation and Ferroptosismentioning
confidence: 99%
“…PGC-1α is likely a pivotal target of SIRT1 due to its transcriptional regulation, with the associated transcription factors encompassing PPARα, PPARγ, FoxO1, Nrf1, Nrf2, etc. [66][67][68][69].…”
Section: The Link Between Neuroinflammation and Ferroptosismentioning
confidence: 99%
“…Performing moderate physical activities, such as walking, jogging, swimming, etc., during the postoperative recovery period is believed to help lower the level of inflammation after general anesthesia and provide protection for cognitive function ( Guszkowska, 2004 ). The latest study has revealed that aerobic exercise combined with chlorogenic acid exerts neuroprotective effects and reverses cognitive decline in the AD model mice (APP/PS1) through the SIRT1/PGC-1α/PPARγ signaling pathway ( Shi et al, 2023 ).…”
Section: Some Preventive Strategies For the Peripheral Inflammation P...mentioning
confidence: 99%